Do photosynthetic limitations of evergreen Quercus ilex leaves change with long-term increased drought severity? (Plant, Cell & Environment, 2010)
Seasonal drought can severely impact leaf photosynthetic capacity. This is particularly important for Mediterranean forests, where precipitation is expected to decrease as a consequence of climate change. Impacts of increased drought on the photosynthetic capacity of the evergreen Quercus ilex were studied for two years in a mature forest submitted to long-term throughfall exclusion. Gas exchange and chlorophyll fluorescence were measured on two successive leaf cohorts in a control and a dry plot. Exclusion significantly reduced leaf water potential in the dry treatment. In both treatments, light-saturated net assimilation rate (Amax), stomatal conductance (gs), maximum carboxylation rate (Vcmax), maximum rate of electron transport (Jmax), mesophyll conductance to CO2 (gm) and nitrogen investment in photosynthesis decreased markedly with soil water limitation during summer. The relationships between leaf photosynthetic parameters and leaf water potential remained identical in the two treatments. Leaf and canopy acclimation to progressive, long-term drought occurred through changes in leaf area index, leaf mass per area and leaf chemical composition, but not through modifications of physiological parameters.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd